Influence of Salinity of Mixing Water Towards Physical and Mechanical Properties of High Strength Concrete - R.A. Razak; K. Yen Ng; M.M. Al Bakri Abdullah; Z. Yahya; R. Mohamed; K. Muthusamy; W.A.W. Jusoh; M. Nabiałek; B. Jeż (Archives of Metallurgy and Materials, 2023)
Dramatic population and economic growth result in increasing demand for concrete infrastructure, which leads to an increment of freshwater demand and a reduction of freshwater resources. However, freshwater is a finite resource, which means that freshwater will be used up someday in the future when freshwater demand keeps increasing while freshwater resources are limited. Therefore, replacing freshwater with seawater in concrete blending seems potentially beneficial for maintaining the freshwater resources as well as advantageous alternatives to the construction work near the sea. There have been few experimental research on the effect of blending water salt content on the mechanical and physical characteristics of concrete, particularly high-strength concrete. Therefore, a research study on the influence of salt concentration of blending water on the physical and mechanical properties of high-strength concrete is necessary. This study covered the blending water salinity, which varied from 17.5 g/L to 52.5 g/L and was determined on the physical and mechanical properties, including workability, density, compressive strength, and flexural strength. The test results indicate that the use of sea salt in blending water had a slight negative influence on both the workability and the density of high strength concrete. It also indicates that the use of sea salt in blending water had a positive influence on both the compressive strength and the flexural strength of high-strength concrete in an earlystage.